ANALISIS PERILAKU ORGANISASI DALAM PENDOKUMENTASIAN ASUHAN KEPERAWATAN DI RUANG RAWAT INAP CENDRAWASIH RUMAH SAKIT UMUM DAERAH (RSUD) ARI - Delta Meda Aba,Budi Hartono, Siska Mayang Sari (Menara Ilmu, 2018)
One of them nurse work is making documentation of nursing care about intervension topatient, but sometime that can change, that efec to focus documentation nuring care.Documentation is a note can make proof in implementation of nursing care. This studyaims to know the organization in the Behavioral Analysis documenting nursing care inpatient wards Cendrawasih Regional General Hospital (RSUD) Arifin Achmad RiauProvince Year 2016.Type of research is qualitative research with in-depth interviews and observation. The dataanalysis is conducted qualitatively descriptive stages of data collection, simplification,data presentation and conclusions.The results of this study are of nurses had not made documentation nursing care, as nurseschoose a high workload. Manager of room will give a warning and asked to complete thedocumentation. Nurses will be warned and advised his friend to complete thedocumentation of nursing care if there is not complete. There is no specific reward fornursing care documentation. No documentation is in accordance with existing guidelines.Documentation has a very important role. The obstacle is the small print, too much, lessemployee or human resources and lack of motivation.The conclusion of the study is no relationship between the input, process and output.Suggestions for writing documentation formatting bigger and clearer, the paymentsrequired.Keywords : Analysis, Organization Behavior, DocumentationBibliography: 32 (2004-2016)